2017
DOI: 10.1038/ncomms14687
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: TRIB2 confers resistance to anti-cancer therapy by activating the serine/threonine protein kinase AKT

Abstract: Intrinsic and acquired resistance to chemotherapy is the fundamental reason for treatment failure for many cancer patients. The identification of molecular mechanisms involved in drug resistance or sensitization is imperative. Here we report that tribbles homologue 2 (TRIB2) ablates forkhead box O activation and disrupts the p53/MDM2 regulatory axis, conferring resistance to various chemotherapeutics. TRIB2 suppression is exerted via direct interaction with AKT a key signalling protein in cell proliferation, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
77
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(88 citation statements)
references
References 25 publications
11
77
0
Order By: Relevance
“…To confirm that recombinant TRIB2 binds to a known physiological target, we demonstrated that GST-tagged TRIB2 interacted with a marked preference for catalytically inactive (non Thr 308-phosphorylated) AKT1 in vitro ( Figure 1C). Consistent with a functional regulatory interaction between TRIB2 and AKT in cells [49], transient overexpression of Tet-inducible FLAGtagged TRIB2 in HeLa cells led to a marked increase in endogenous AKT phosphorylation at the hydrophobic motif (Ser 473, Figure 1D), an established marker for AKT catalytic activity and the downstream generation of a cellular anti-apoptotic signal [50].…”
supporting
confidence: 62%
See 2 more Smart Citations
“…To confirm that recombinant TRIB2 binds to a known physiological target, we demonstrated that GST-tagged TRIB2 interacted with a marked preference for catalytically inactive (non Thr 308-phosphorylated) AKT1 in vitro ( Figure 1C). Consistent with a functional regulatory interaction between TRIB2 and AKT in cells [49], transient overexpression of Tet-inducible FLAGtagged TRIB2 in HeLa cells led to a marked increase in endogenous AKT phosphorylation at the hydrophobic motif (Ser 473, Figure 1D), an established marker for AKT catalytic activity and the downstream generation of a cellular anti-apoptotic signal [50].…”
supporting
confidence: 62%
“…Afatinib (and neratinib) reduced cell viability with sub-micromolar IC50 values, whereas EGFR inhibitors erlotinib and gefitinib and the dual EGFR/HER2 inhibitor TAK-285, were 10-20 fold less effective when compared side-by-side ( Figure 5C). As these compounds did not induce TRIB2 destabilization, AKT activation or caspase 3 activation, our data suggest that the cellular TRIB2-destabilizing ligands afatinib and neratinib possess an enhanced ability to kill AMLderived cells [49].…”
Section: Evaluation Of Trib2 Ligands In Human Cellsmentioning
confidence: 68%
See 1 more Smart Citation
“…As described previously, TRIB2 promotes tumorigenesis and induces therapeutic resistance by activating Wnt‐mediated downstream activation of Hippo signaling and the YAP pathway through transcriptional control of gene expression and TRIB2‐mediated posttranslational regulation of protein stability in liver cancer cells . Richard et al indicated that TRIB2 enhances the tumorigenesis of melanoma cells by negatively regulating p21 and p53 in an AKT serine/threonine kinase‐dependent manner. In addition to the analysis of published gene profiles, we also validated our findings using clinical samples obtained from patients with glioma.…”
Section: Discussionmentioning
confidence: 79%
“…Moreover, Wnt/TCF signaling-dependent activation of TRIB2 stimulates the proliferation of liver cancer cells through a stabilization effect on yes-associated protein (YAP). 10 Hou et al 7 found that TRIB2 increases colorectal cancer tumor growth by decreasing the expression of p21, which functions as a tumor suppressor gene, indicating that TRIB2 could become a potential molecular target for colorectal cancer. These studies prompted the hypothesis that TRIB2 is a prognostic predictor for multiple types of malignant tumors.…”
mentioning
confidence: 99%